The elements of style - Strunk, William (Ithaca, N.Y Priv. print, 2014)
The Elements of Style by William Strunk, Jr. is a prescriptive American English writing style guide comprising eight "elementary rules of usage", ten "elementary principles of composition", "a few matters of form", a list of forty-nine "words and expressions commonly misused", and a list of fifty-seven "words often misspelled". In 2011, Time magazine listed The Elements of Style as one of the 100 best and most influential books written in English since 1923
Keywords: English language --Rhetoric.